1998
DOI: 10.1097/00002030-199808000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii mutations associated with sulfa and sulfone prophylaxis failures in AIDS patients

Abstract: Mutations in two amino-acid positions were significantly more common in AIDS patients with PCP who failed sulfa/sulfone prophylaxis. These amino acids appeared to be directly involved in both substrate and sulfa binding, based on homology to the Escherichia coli DHPS crystal structure. Thus, the results were consistent with the possibility that mutations in the P. carinii DHPS are responsible for some of the failures of sulfa/sulfone prophylaxis in AIDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
189
5
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(213 citation statements)
references
References 18 publications
17
189
5
2
Order By: Relevance
“…Prior exposure to sulfonamide drugs has been identified as a predictor of mutant genotypes (reviewed in Totet et al, 2004). In addition the city in which a patient resides has also been identified as an independent risk factor (Huang et al, 2000;Kazanjian et al, 2000), a factor that supports the hypothesis that P. jirovecii is transmitted from infected treated patients to susceptible untreated patients, either directly or through a common envi-ronmental source. Totet and colleagues identified P. jirovecii genotypes at the DHPS locus in immunocomptetent infants with primary infection and immunosuppressed adults with PCP (Totet et al, 2004).…”
Section: Transmission Of Possible Resistant P Jirovecii Organisms Inmentioning
confidence: 99%
“…Prior exposure to sulfonamide drugs has been identified as a predictor of mutant genotypes (reviewed in Totet et al, 2004). In addition the city in which a patient resides has also been identified as an independent risk factor (Huang et al, 2000;Kazanjian et al, 2000), a factor that supports the hypothesis that P. jirovecii is transmitted from infected treated patients to susceptible untreated patients, either directly or through a common envi-ronmental source. Totet and colleagues identified P. jirovecii genotypes at the DHPS locus in immunocomptetent infants with primary infection and immunosuppressed adults with PCP (Totet et al, 2004).…”
Section: Transmission Of Possible Resistant P Jirovecii Organisms Inmentioning
confidence: 99%
“…Other drugs including dapsone, atovaquone and pentamidine are alternatives to TMP/SMX, but they are either more toxic or less active against P. jirovecii (Hughes et al, 1993;Hughes, 1998;Kovacs et al, 2001a;Sattler et al, 1988;Vasconcelles et al, 2000). Unfortunately, recent studies have identified mutations in the gene encoding DHPS suggesting the emergence of resistance in P. jirovecii to sulfa drugs (dapsone and SMX) (Helweg-Larsen et al, 1999;Kazanjian et al, 2000;Ma et al, 1999;Navin et al, 2001). Development of new drugs to treat or prevent PCP thus remains an important priority for research.…”
Section: Introductionmentioning
confidence: 99%
“…[ [11][12][13] Terbinafine is an allylamine agent which appears to act by preventing fungal ergosterol biosynthesis via specific and selective inhibition of fungal sequalene epoxidase. [3,4] It is orally and topically active especially on dermatophyte, filamentous, dimorphic and dematiaceous fungi, and some yeast species.…”
Section: Discussionmentioning
confidence: 99%